2017
DOI: 10.1016/j.jamcollsurg.2016.12.058
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Chemotherapy Combined with Resection for Locally Advanced Gallbladder Carcinoma: Surgical and Survival Outcomes

Abstract: Background Preoperative chemotherapy is a strategy for conversion to resection and/or assessing disease biology prior to operation. The utility of such an approach in gallbladder carcinoma (GBCA) is unknown. This study evaluates outcomes of GBCA patients treated with chemotherapy for locally advanced or lymph node involved tumors. Study Design Patients that received systemic chemotherapy for locally advanced or lymph node positive GBCA were identified from a departmental database. Patients were excluded if t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 23 publications
1
40
0
1
Order By: Relevance
“…Similar study from MSKCC group in 74 locally advanced GBC patients reported significantly improved median OS of 51 months for 10 patients who HPB underwent definitive resection after NACT and 14 months for the entire cohort. 21 Chemotherapy provided a significant survival benefit even in a group of patients with unresectable SD post NACT proving that benefit of chemotherapy was sustained across all groups. CA 19.9 levels and liver infiltration were significant only on univariate analysis.…”
Section: Discussionmentioning
confidence: 93%
“…Similar study from MSKCC group in 74 locally advanced GBC patients reported significantly improved median OS of 51 months for 10 patients who HPB underwent definitive resection after NACT and 14 months for the entire cohort. 21 Chemotherapy provided a significant survival benefit even in a group of patients with unresectable SD post NACT proving that benefit of chemotherapy was sustained across all groups. CA 19.9 levels and liver infiltration were significant only on univariate analysis.…”
Section: Discussionmentioning
confidence: 93%
“…Sirohi et al reported a 65% response rate with a 40% R0 resection rates in patients with Gem‐CIs/Gem‐Ox neoadjuvant chemotherapy for locally advanced patients with GBC. Creasy et al from Memorial Sloan Kettering Cancer center reported a 14% curative resection rate with a significantly improved overall survival in the resection group (51 months [95% CI, 11.7‐55.3] vs 11 months [95% CI, 4.1‐23.6] P = 0.003). Both these studies included all the patients with locally advanced GBC and not exclusively those with jaundice.…”
Section: Discussionmentioning
confidence: 99%
“…Because LN positivity is comparable between the primary and validation cohorts, our results suggest that the aggressiveness of BTCs. Neoadjuvant therapy may be indicated for tumors with high risk of LN metastasis to evaluate tumor biology and defined patient subsets most likely to benefit from surgical treatment (30,31).…”
Section: Preoperative Predictors Of Survivalmentioning
confidence: 99%